HOW TO TRANSLATE A DREAM : PRAGMATIC ASPECTS OF PROMOTIONAL TEXT TRANSLATION - Smirnova, Tatjana (Vertimo studijos, 2017)
The present article provides some insights into the issues concerning the translation of advertising slogans. Application of phonetic stylistic devices and the effects their usage cause are studied analyzing slogans in English, Latvian and Russian. The analysis is undertaken with an aim to consider the role of phonetic stylistic devices in operative texts, with the focus on advertising slogans, and to identify the most appropriate translation methods to be applied in the rendition of these devices in operative texts across the working languages to ensure the equivalence of the intended effect of the source and target message.